Migraine Aura and Exercise - Appenzeller, Otto (British Journal of Healthcare and Medical Research, 2024)
In this self-report I find that the aura of migraine is prolonged by exercise from 3 minutes to 11 minutes. I discuss the possible causes and implications for patient management.